Public Reception of Qur'an Calligraphy at the Iska Mayang Grand Mosque in Sukoharjo - Siyamto, Muhammad Rasyid Ridlo; Rhain, Ainur; Ilham, Muhammad; Wakit, Saipul (QiST: Journal of Quran and Tafseer Studies, 2025)
The holy book of the Quran has an informative and performative function. The informative function refers to the purpose of conveying the message or information of the Qur'an text itself. While the performative function refers to how the Qur'an can create emotional, spiritual, and aesthetic impacts that go beyond simply reading texts. Qur'an calligraphy includes two functions at once, namely when people use calligraphy as a means of conveying revelation and expression of Islamic art, for example Qur'an calligraphy which decorates many mosques around the community. The Iska Grand Mosque in Sukoharjo is known as one of the mosques decorated with Qur'an calligraphy, beautifying every corner of the building. This situation provides an opportunity for the community around the mosque to explore the meaning implied in the art of Qur'an calligraphy. This study centers on how the community responds to and accepts the existence of Qur'an calligraphy in the mosque. The purpose of this investigation is to find out the responses or views of readers and calligraphy connoisseurs at the Iska Mayang Sukoharjo Grand Mosque. This study adopts a qualitative method through a descriptive approach to reveal data in depth (Living Qur'an) which is supported by various literature sources. The findings of this study reveal that calligraphy contributes to linking the interpretation of the content of Qur'anic verses with aesthetic elements, as well as providing an overview of how people judge and enjoy the art of calligraphy at the Iska Grand Mosque. The calligraphy written is a type of khat tsulus in the form of verse writing from Surah Al-Baqarah verse 255, verses 43-44, and Al-Mu'minun verses 1-4.